2018
DOI: 10.35923/jes.2018.2.05
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive coping strategy in situations of social conflict. an attempt to determine personality predictors

Abstract: The purpose of the study was to find personality predictors of aggressive coping strategies in adolescents in situations of social conflict. The empirical studies have been conducted in junior high schools on a sample of 893 adolescents (468 girls and 425 boys) aged 13-15. The study employed the following instruments: the Stress Assessment Questionnaire (Kwestionariusz Oceny Stresu, KOS) designed by D. Włodarczyk and K. Wrześniewski, The Rosenberg designed by D. Borecka-Biernat. The results of the studies indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…Por otro lado, existen una serie de estrategias de afrontamiento que pueden clasificarse como inadecuadas, debido al carácter evitativo del problema de las mismas. Este tipo de estrategias de afrontamiento se relacionan con el uso de conductas agresivas o emociones negativas a la hora de dar respuesta a un determinado conflicto, así como, la falta de hacer frente al problema mediante la evitación (Borecka-Biernat, 2018;Bosworth & Hammer, 1995;Matthews et al, 2016;Rodríguez et al, 2016;Vashchenko et al, 2007). Además, es necesario resaltar la existencia de diferencias en relación con las estrategias de afrontamiento según tanto el sexo como la edad.…”
Section: Discusión Y Conclusionesunclassified
“…Por otro lado, existen una serie de estrategias de afrontamiento que pueden clasificarse como inadecuadas, debido al carácter evitativo del problema de las mismas. Este tipo de estrategias de afrontamiento se relacionan con el uso de conductas agresivas o emociones negativas a la hora de dar respuesta a un determinado conflicto, así como, la falta de hacer frente al problema mediante la evitación (Borecka-Biernat, 2018;Bosworth & Hammer, 1995;Matthews et al, 2016;Rodríguez et al, 2016;Vashchenko et al, 2007). Además, es necesario resaltar la existencia de diferencias en relación con las estrategias de afrontamiento según tanto el sexo como la edad.…”
Section: Discusión Y Conclusionesunclassified
“…Adolescents use a range of coping strategies when faced with conflict. Frydenberg and Lewis (2000) identified various types: seeking a solution in the face of conflict, seeking social support (from family, peers, or professionals), avoidance strategies, distancing from the problem, and even aggression and/or anger (Borecka-Biernat 2018). Other studies have shown that gender has an influence on conflict management; thus, Çoban (2013), Verdugo-Lucero et al (2013), andReyes et al (2017) found that the strategy most used by females was seeking support, while males often resorted to conflict avoidance.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical evidence suggests that clinicians guide CHD patients by improving their coping skills to reduce these negative emotions. 12 Researchers suggest that Individuals with type B behavior patterns could not better cope with these stressors as well as individuals with type A behavior patterns. 13 Problem-focused coping strategies are more used in men and women than emotion-focused strategies in patients with CHD.…”
Section: Introductionmentioning
confidence: 99%